Understanding the sociality of child marriage. Issue 5 (3rd July 2020) - Sharma, Rachana; Shukla, Arupa; Sriram, Dhuwarakha; Ramakrishnan, Vimala; Kalaan, Mandira; Kumar, Archna
ABSTRACT: Social norms can have a significant impact on prevalent attitudes towards child marriage and the education of adolescent girls. This article reports on a quantitative study in the Indian states of Jharkhand, West Bengal, Andhra Pradesh, and Assam, that highlighted that social norms played a greater role than economic wealth in related decision-making. Adolescents experienced social norms both through their own interactions with the larger community and through their parents' attitudes, especially in the case of girls. Interventions targeting adolescents need to factor in societal structures, historical marginalisation, and norms that influence adolescents and their families at the family and community levels.